2020
DOI: 10.3906/sag-1809-108
|View full text |Cite
|
Sign up to set email alerts
|

The utility of synovial fluid levels of ADAMTS9 and ADAMTS4 in predicting treatment responses to intraarticular steroid injections in patients with knee osteoarthritis

Abstract: Background/aim This study aims to identify the role of synovial fluid levels of a disintegrin and metalloproteinase with thrombospondin motifs 9 (ADAMTS9) and a disintegrin and metalloproteinase with thrombospondin motifs 4 (ADAMTS4) for the prediction of intraarticular steroid injection success in knee osteoarthritis (OA). Material and methods A total of eighty-four advanced stage knee OA patients (42 with stage 3 OA and 42 with stage 4 OA) were enrolled in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…They concluded that ADAMTS‐4 in mild OA patients was significantly higher than in other advanced OA groups and healthy controls 22 . Significance of synovial fluid ADAMTS‐4 and ‐9 levels in OA progression were evaluated, and no significant differences were found in ADAMTS‐4 synovial fluid levels of stage 3 and 4 OA patients 23 . The pathogenesis of articular cartilage damage in the two aforementioned conditions may have a different pattern that entails a different expression profile of molecules that are activated and lead to damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that ADAMTS‐4 in mild OA patients was significantly higher than in other advanced OA groups and healthy controls 22 . Significance of synovial fluid ADAMTS‐4 and ‐9 levels in OA progression were evaluated, and no significant differences were found in ADAMTS‐4 synovial fluid levels of stage 3 and 4 OA patients 23 . The pathogenesis of articular cartilage damage in the two aforementioned conditions may have a different pattern that entails a different expression profile of molecules that are activated and lead to damage.…”
Section: Discussionmentioning
confidence: 99%
“…22 Significance of synovial fluid ADAMTS-4 and -9 levels in OA progression were evaluated, and no significant differences were found in ADAMTS-4 synovial fluid levels of stage 3 and 4 OA patients. 23 The pathogenesis of articular cartilage damage in the two aforementioned conditions may have a different pattern that entails a different expression profile of molecules that are activated and lead to damage. As previously mentioned, the study by Li et al found elevated serum levels of ADAMTS-4 in mild OA forms, 22 which is in contrast to our findings, which show larger individual levels in severe OA compared to mild disease forms; the largest increase was observed in the group of patients with HA, which was not thus far explored by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Daha önceki bir çalışmada osteoartrit (OA) hastalarının kıkırdak dokusunda ADAMTS9 ve ADAMTS15 genlerinin ekspresyon düzeylerinin normal kıkırdak dokusuna göre önemli derecede azaldığı rapor edilmiştir (22). Başka bir çalışmada, OA' li hastaların sinovial sıvısında ADAMTS9 düzeylerinin azaldığı ve intraartiküler tedaviye yanıtın izlenmesinde ADAMTS9 düzeylerininin belirteç olabileceği ifade edilmiştir (23). Kronik inflamatuar romatoik bir hastalık olan Spondiliarthritis (SpA) de, hastaların dentritik hücrelerinde ADAMTS15 gen ekspresyonunun artış gösterdiği ve bu artışın doku inflamasyonu ve hasarı ile ilişkili olabileceği bildirilmiştir (24).…”
unclassified